Identifikasi Karakteristik Ruang Bersama pada Permukiman Nelayan Untuk Optimalisasi Peremajaan Permukiman dengan Konsep Co-Living (Studi Kasus Kelurahan Kangkung, Kota Bandar Lampung) - Hafi Munirwan; Antusias Nurzukhrufa; Fadila Septiandiani; Cindy Dwi Islami (Universitas Batanghari Jambi, 2021)
Housing and settlements are basic needs of every human being as a place to grow and develop. In developing countries, rapid population growth results in scarcity of land and housing, especially for low-income people. Thus, slums grow on the top, edges, plains, hills and disaster-prone areas. Various initiatives to rejuvenate slums have been carried out, but have not completely succeeded in eliminating slums. Limited institutional and funding resources require an innovative approach in rejuvenating slum settlements to be more efficient, which has a significant impact on the community. The characteristics of slum settlements that are dense and have a limited residential area also require innovation to meet decent housing standards. In addition, the value of togetherness and the high level of social interaction between residents of urban villages is a potential that can be integrated in the rejuvenation of slums. In line with these challenges and potentials, co-living, the concept of living together, by sharing space for common use, is an approach that can be applied in efforts to rejuvenate settlements. As a maritime and archipelagic country, one of the characteristics of settlements that often develop in Indonesia is fishermen's settlements in coastal areas. In this study, a study was conducted on the common spaces in the fishermen's settlement of Kangkung Village, Bandar Lampung. This common room is usually used by the community to interact or carry out their activities either in the morning, afternoon, evening or night. The purpose of this study is to identify the characteristics of the common space in fishing settlements, as well as the characteristics of its users. The handling of this common space can be prioritized to improve the social and economic conditions of the community, while at the same time providing a significant impact not only for individuals, but also for wider community groups. The research method used in this study is a qualitative inductive approach, with data sourced from field observations and interviews with stakeholders in fishing settlements, both community and government representatives. The results of this study have identified at least five shared spaces in the fishing settlements of Kangkung Village, namely markets, ports and fish auction sites (TPI), waterfront areas, road corridors and public toilets.